Numerický model oceňování evropské kupní opce - Seinerová, Kateřina (Univerzita Pardubice, 2010)
In this paper a mathematical model of European call options prizing is presented. This model is based on reduced Black-Scholes partial differential equation, discretized employing the finite difference method. The results of this model and of the exact solution of Black-Scholes equation are compared.
Keywords: Black-Scholes schema; European call options; PDE; Finite Difference Method